Meningkatkan Literasi Digital Siswa SMA Baitul Hikmah di Tarogong Kaler, Kabupaten Garut, melalui Program Edukasi dan Kesadaran akan Penggunaan Media Digital yang Bijak - Rukmana, Ade; Nurpadillah, Sifa; Nurichsan, Irman; Wijaya, Beni; Helma, Yayang; Sani, Sani Mochsopian (Universitas Hamzanwadi, 2025)
This community outreach program seeks to improve digital literacy among students at Baitul Hikmah Senior High School in Tarogong Kaler, Garut, who are facing challenges in using technology effectively. The primary goal of this initiative is to enhance students’ understanding of digital literacy by emphasizing responsible internet behavior and encouraging critical thinking when evaluating information. The program includes an initial assessment, distribution of digital literacy content, interactive Q&A sessions, and a follow-up evaluation. Findings show that students' understanding improved, with post-program scores showing a marked increase compared to their earlier assessments. This initiative contributes significantly to developing students’ recognition of the value of digital literacy, enabling them to better engage in both academic settings and daily life in the digital era.